Parchemins. - Bonfand, Alain; Boulot, Yannick; Celan, Paul; Cousseau, Henry-Claude; Lanzenberg, Anthony; Minière, Claude; Penone, Giuseppe; Semin, Didier; Vincendeau, Jean-Louis (Paris : Ecole Nationale Supérieure des Beaux-Arts Paris, 2003)
Penone, Giuseppe ; Bonfand, Alain ; Boudvin, Simon ; Boulot, Yannick ; Budewick, Martha ; Celan, Paul ; Dietrich, Cyril ; Elaloussi, Mounir ; Glasner, Killian ; Kohira, Atsunobu ; Lanzenbeg, Anthony ; Lehodey, Stéphane ; Ly, Nicolas ; Minière, Claude ; Paul, Emeric Frédéric ; Robalino, Carla ; Rotaru, Irina ; Sabourin, Thomas ; Sartore, Cédric ; Semin, Didier ; Starke, Susanne ; Soy ; Trepagne, Bénédicte ; Vincendeau, Jean-Louis
Frans
Exhibition. Parchemins, atelier de Giuseppe Penone. Jardin Shakespeare Paris. Ecole Nationale Supérieure des Beaux-Arts Paris. 2003
boek